FRI0436 CCPA Reverses the Fibrotic Phenotype of Dermal Fibroblasts in Systemic Sclerosis. (9th June 2015) - Higuchi, T.; Kawaguchi, Y.; Masuda, I.; Takagi, K.; Tochimoto, A.; Yamanaka, H.; Okada, K.
Abstract : Background: Systemic Sclerosis (SSc) is a connective tissue disease with excessive fibrosis that affects the skin and various internal organs. Skin fibrosis is one of the main manifestations of SSc, however, the therapeutic strategy has not been established merely because the fibrotic mechanisms in the affected skin has not been fully elucidated. An autotaxin (ATX)/lysophosphatidic acid (LPA) axis has emerged as a novel pathogenic factor in various fibrotic disorder including SSc [1]. Cyclic phosphatidic acid (CPA), which is catalyzed by ATX as well as LPA, shows several distinct activities from LPA such as the inhibitory effects of proliferation, invasion and metastasis of cancer cells [2]. In addition, CPA has been reported to inhibit ATX activity and then, LPA production. These findings suggest that CPA may be a potent agent to ameliorate fibrosis. Objectives: The aim of our study was to investigate the anti-fibrotic property of metabolically stabilized carba derivatives of CPA (CCPA) in dermal fibroblasts from patients with SSc. Methods: Primary human dermal fibroblasts obtained from SSc patients or healthy individuals were incubated with CCPA in the presence or absence of TGF-β1 or LPA. The mRNA levels of COL1A1, COL1A2, CTGF, ACTA2, fibronectin ( FN ), MMP-1, endothelin-1 (ET-1), IL-6 and TGF-β1 were assessed using quantitative real-time RT-PCR. In addition, the protein levels of type I collagen, CTGF and αSMA in cell lysates were evaluated using Western blotting. To examine the effects of CCPA on the Smad and the MAPK signaling pathway, the expression of total and phosphorylated Smad2/3, p38 and ERK1/2 were detected using Western blotting. Results: CCPA significantly decreased the expression of COL1A1, COL1A2, CTGF, ACTA2 and FN mRNA in SSc- and healthy-dermal fibroblasts stimulated by TGF-β1 in a concentration dependent manner, whereas the expression of MMP-1 mRNA was increased. Furthermore, the expression of TGF-β1, ET-1 and IL-6 mRNA was significantly down-regulated at 24h after the treatment with CCPA. The protein levels of type I collagen, CTGF and αSMA were also significantly reduced by CCPA. These effects were shown without the stimulation of LPA. CCPA suppressed the phosphorylation of p38 and ERK1/2, suggesting that the anti-fibrotic effects of CCPA were in part through MAPK signaling pathways. Conclusions: We demonstrated for the first time that CCPA reversed the fibrotic phenotype of SSc dermal fibroblasts. Intriguingly, CCPA showed anti-fibrotic effects in SSc dermal fibroblasts without the stimulation of LPA, suggesting that CCPA has pleiotropic effects other than antagonizing the ATX/LPA axis. CCPA would be a novel therapeutic strategy for the treatment of skin fibrosis of SSc. References: Castelino F, et al. Arthritis Rheum 2011;63:1405-15. Baker D, et al. J Biol Chem 2006;281:22786-93. Disclosure of Interest: None declared